Good morning, destroyer of men's souls : a memoir of women, addiction, and love - Aron, Nina Renata (Crown, 2020)
"A scorching memoir of a love affair with an addict, weaving personal reckoning with psychology and history to understand the nature of addiction, codependency, and our appetite for obsessive love. "The disease he has is addiction," Nina Renata Aron writes of her boyfriend, K. "The disease I have is loving him." Their love affair is dramatic, urgent, overwhelming-an intoxicating antidote to the long, lonely days of early motherhood. Soon after they get together, K starts using again, and years of relapses and broken promises follow. Even as his addiction deepens, she stays, convinced she is the one who can get him sober. After an adolescence marred by family trauma and addiction, Nina can't help but feel responsible for those suffering around her. How can she break this pattern? If she leaves K, has she failed him? Writing in prose at once unflinching and acrobatic, Aron delivers a piercing memoir of romance and addiction, drawing on intimate anecdotes as well as academic research to crack open the long-feminized and overlooked phenomenon of codependency. She shifts between visceral, ferocious accounts of her affair with K and introspective analyses of the part she plays in his addictions, as well as defining moments in the history of codependency, from the temperance movement to the formation of Al-Anon to more recent research in the psychology of addiction. Good Morning, Destroyer of Men's Souls is a blazing, bighearted book that illuminates and adds nuance to the messy tethers between femininity, enabling, and love"--